2019
DOI: 10.15255/cabeq.2019.1632
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Cefdinir from Aqueous Solution Using Nanostructure Adsorbents of TiO2, SiO2 and TiO2/SiO2

Abstract: The adsorptive removal of cefdinir, an antibiotic, from aqueous solutions on TiO2, SiO2 and TiO2/SiO2 nanostructures was studied by batch experiments. The SiO2 particles were obtained from rice husk ash. Investigated were the effects of the solution pH, adsorbent dosage, initial adsorbate concentration, and solution temperature on both cefdinir uptake and removal. The studies suggest that the adsorption of cefdinir on the nanostructures was mainly due to the electrostatic interaction between the ionic adsorbat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Also, this process is physical because for physical adsorption ∆ H 0 < 35.0 kJ mol −1 and chemical adsorption ∆ H 0 > 35.0 kJ mol −1 . Δ S 0 values were determined to be 130, 27, and 84 J mol −1 K −1 for raw AC, CHT:AEO, and CHT:AEO:AC, respectively, and the positive Δ S 0 values reflect increased randomness at the solid–liquid interface during the process (Yener, 2019). Also, the negative ∆ G 0 values show that the naproxen adsorption on all biocomposites is feasible and spontaneous.…”
Section: Resultsmentioning
confidence: 99%
“…Also, this process is physical because for physical adsorption ∆ H 0 < 35.0 kJ mol −1 and chemical adsorption ∆ H 0 > 35.0 kJ mol −1 . Δ S 0 values were determined to be 130, 27, and 84 J mol −1 K −1 for raw AC, CHT:AEO, and CHT:AEO:AC, respectively, and the positive Δ S 0 values reflect increased randomness at the solid–liquid interface during the process (Yener, 2019). Also, the negative ∆ G 0 values show that the naproxen adsorption on all biocomposites is feasible and spontaneous.…”
Section: Resultsmentioning
confidence: 99%
“…[ 41 ] The degree of ionization of cefdinir is expected to increase with an increase in the pH of the solution. [ 28 ] The WL‐BC‐OH sample exhibited good performance in a wide pH range (2–11), and the cefdinir adsorption capacity of WL‐BC‐OH did not change significantly with the change in pH. This may indicate that a change in pH had a minimal effect on the surface chemistry charges of WL‐BC‐OH.…”
Section: Resultsmentioning
confidence: 99%
“…Recent reviews have reported that the pseudo‐second‐order kinetic model was the major fitted model for antibiotic adsorption on BC. [ 28,45,46 ] However, some studies also reported that the pseudo‐first‐order model fitted the experimental data. [ 47 ]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation